Running-based anaerobic sprint test as a procedure to evaluate anaerobic power - Andrade, V. L.; Zagatto, A. M. [UNESP]; Kalva-Filho, C. A.; Mendes, O. C.; Gobatto, C. A.; Campos, E. Z. [UNESP]; Papoti, M. (Georg Thieme Verlag KG Stuttgart · New York., 2015)
The aim of this study was to evaluate the use of the running anaerobic sprint test (RAST) as a predictor of anaerobic capacity, compare it to the maximal accumulated oxygen deficit (MAOD) and to compare the RAST's parameters with the parameters of 30-s all-out tethered running on a treadmill. 39 (17.0±1.4 years) soccer players participated in this study. The participants underwent an incremental test, 10 submaximal efforts [50-95% of velocity correspondent to VO2MAX (vVO2MAX)] and one supramaximal effort at 110% of vVO2MAX for the determination of MAOD. Furthermore, the athletes performed the RAST. In the second stage the 30-s all-out tethered running was performed on a treadmill (30-s all-out), and compared with RAST. No significant correlation was observed between MAOD and RAST parameters. However, significant correlations were found between the power of the fifth effort (P5) of RAST with peak and mean power of 30-s all-out (r=0.73 and 0.50; p<0.05, respectively). In conclusion, the parameters from RAST do not have an association with MAOD, suggesting that this method should not be used to evaluate anaerobic capacity. Although the correlations between RAST parameters with 30-s all-out do reinforce the RAST as an evaluation method of anaerobic metabolism, such as anaerobic power.
Keywords: Maximal accumulated oxygen deficit; Anaerobic metabolism; Anaerobic performance; Maximal sprint